2017
DOI: 10.18203/issn.2454-5929.ijohns20171190
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of noise induced hearing loss in a tertiary care hospital of Jharkhand - an alarming but ignorant truth

Abstract: <p class="abstract"><strong>Background:</strong> Noise induced hearing loss (NIHL) is hearing impairment resulting from exposure to loud sound. People may have a loss of perception of a narrow range of frequencies, impaired cognitive perception of sound, or other impairment, including sensitivity to sound or ringing in the ears. NIHL is 2<sup>nd</sup> most common cause of hearing loss, next to presbycusis. Most of the population of developing countries is ignorant of the hazards o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…The risks of hearing loss due to noise exposure were quite common; as a result, over 42.07% of the employees examined in our study had abnormal audiograms. Mild hearing loss was the most commonly reported NIHL, 20 which is consistent with our findings. In contrast to the findings of this study, Bhatt and Guthrie reported that 55.6% of their study sample had a 4-6 kHz notch in at least one ear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The risks of hearing loss due to noise exposure were quite common; as a result, over 42.07% of the employees examined in our study had abnormal audiograms. Mild hearing loss was the most commonly reported NIHL, 20 which is consistent with our findings. In contrast to the findings of this study, Bhatt and Guthrie reported that 55.6% of their study sample had a 4-6 kHz notch in at least one ear.…”
Section: Discussionsupporting
confidence: 92%
“…According to some surveys, age, gender, and noise exposure, all have a significant impact on audiometric notches. 19,20 Our findings revealed a substantial relationship between age and experience and the bilateral moderate 4 kHz notch. This revealed that NIHL is a symptom or feature of the 4 kHz notch, namely, the bilateral notch (NMo).…”
Section: Discussionmentioning
confidence: 54%
“…In a study conducted in a hospital setting in Northern India, 54% complained solely of hearing loss, while the other half complained of tinnitus and hearing loss. 15 In the same study, NIHL binaural involvement was observed in 74%, which is similar to our study, 78.57%. In a police survey, only 61.64% had a binaural association, which is lower than our study.…”
Section: Discussionsupporting
confidence: 90%